1977
DOI: 10.1016/s0022-5347(17)58181-1
|View full text |Cite
|
Sign up to set email alerts
|

Cystoplasty by Regeneration of the Bladder

Abstract: Herein we describe a new method for cystoplasty, making use of the regenerating ability of the bladder. The contracted bladder is opened with a crucial incision and enlarged by placing thin paper covered with liquid synthetic resin (nobecutane) like a cap over the opened bladder tissue. Within 3 to 4 weeks granulated tissue completely covers the artificial cap, which is then removed transurethrally. Thereafter, the bladder regenerates on its own. The operation has been done at our hospital from 1970 to 1975 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 4 publications
0
16
0
1
Order By: Relevance
“…It is sometimes reported that the bladder 'regenerates' after a cystoplasty, some centers even use the regenerat ing ability of the bladder in the treatment of contracted bladders by a special cystoplasty using artificial material over which the bladder regenerates [10]. In 1 of our patients (with interstitial cystitis) extensive regeneration of the bladder occurred, which necessitated a revision of the coecocystoplasty.…”
Section: Discussionmentioning
confidence: 79%
“…It is sometimes reported that the bladder 'regenerates' after a cystoplasty, some centers even use the regenerat ing ability of the bladder in the treatment of contracted bladders by a special cystoplasty using artificial material over which the bladder regenerates [10]. In 1 of our patients (with interstitial cystitis) extensive regeneration of the bladder occurred, which necessitated a revision of the coecocystoplasty.…”
Section: Discussionmentioning
confidence: 79%
“…[2][3][4][5][6][7][8] The earliest clinical trials of bladder augmentation by biomaterials were performed in the 1960s and 1970s for bladders after partial cystectomy for invasive bladder cancer, or for contracted bladders due to tuberculosis, which was still prevalent in many countries. 9,10 Thus, it is not surprising that such an approach lost clinical and academic impact during the 1980s and early 1990s, when urinary tuberculosis had nearly disappeared in developed countries, and total cystectomy was established as the standard surgical therapy for invasive cancer. During the same period , the evolution in continent reservoir and neobladder using the digestive tract was so radical that bladder substitution by nonautologous tissue may not have been felt as keenly needed as earlier.…”
Section: Introductionmentioning
confidence: 99%
“…However, the fact that gelatin sponge has not been used since then in further clinical trials of bladder augmentation indicates skepticism about the reliability of the presented results. These doubts have been confirmed by Taguchi et al [127] who showed that the gelatin sponge disintegrated into small pieces in vivo. In combination with nobecutane it formed synthetic resin-like structures and did not degrade, forming calculi in the tissue.…”
Section: Clinical Bladder Tissue Engineeringmentioning
confidence: 88%